2020
DOI: 10.3390/nu12092600
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Uric Acid Levels, Nutritional and Antioxidant Status in Patients on Hemodialysis

Abstract: Purpose: To determine the relationship between uric acid (UA) and nutritional and antioxidant status in hemodialysis (HD) patients, given that hyperuricemia could be an indicator of good nutritional status possibly because of the antioxidant properties of UA. Methods: Cross-sectional study with 93 patients on HD. Hyperuricemia was considered as UA ≥6.0 mg/dL in females and ≥7.0 mg/dL in males. Nutritional variables were registered. Blood samples were taken before the dialysis session to determine oxidative dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Some limitations of this study are the short half-lives of TAC. Nevertheless, some studies report the measurement of this biomarker from serum samples [ 42 44 ]. Moreover, MDA is an end product of lipid peroxidation; thus, it is stable and has a long half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations of this study are the short half-lives of TAC. Nevertheless, some studies report the measurement of this biomarker from serum samples [ 42 44 ]. Moreover, MDA is an end product of lipid peroxidation; thus, it is stable and has a long half-life.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SUA has strong antioxidant properties, as 60% of the free radical scavenging ability of human plasma is derived from the role of SUA [ 9 ]. Domínguez [ 17 ] confirmed that patients on hemodialysis with hyperuricemia had higher antioxidant capacity and less oxidative damage, and they also had better nutritional status in general, mainly according to impedance vectors. When the SUA level is too low, its antioxidant capacity is weakened and oxidative stress is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, poor appetite was associated with an elevated level of inflammatory markers and poor outcomes in HD patients [53]. Furthermore, the benefit of UA could also result from its antioxidant properties [54, 55].…”
Section: Discussionmentioning
confidence: 99%